The Effect of Online Customer Reviews, Online Customer Ratings, and Influencers on Purchase Decisions - Sekar Ayu Agustina; Ralina Transistari (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
This study aims to determine the influence of online consumer reviews, online customer ratings, and influencers on purchase decisions among Shopee consumers. The sampling was conducted using a non-probability sampling technique with a purposive sampling approach. The study was carried out in November 2022, with a total sample size of 160 respondents. The criteria used to select respondents for this study were females who are Shopee account holders, have made fashion product purchases on the platform, and are aged between 18 to 25 years old. The data analysis technique used for this study was multiple linear regression. The results of this study indicates that: online consumer reviews have a positive effect on purchase decisions, online customer ratings also have a positive effect on purchase decisions, and Shopee influencers also have a positive effect on purchase decisions.